2016
DOI: 10.5114/kitp.2016.58960
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and economical benefits of blood patch pleurodesis in secondary spontaneous pneumothorax patients

Abstract: IntroductionProlonged air leak in secondary spontaneous pneumothorax (SSP) patients remains one of the biggest challenges for thoracic surgeons. This study investigates the feasibility, effectiveness, clinical outcomes, and economical benefits of the autologous blood patch pleurodesis method in SSP.Material and methodsFirst-episode SSP patients undergoing autologous blood patch pleurodesis for resistant air leak following underwater-seal thoracostomy, between January 2010 and June 2013 were taken into the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 15 publications
0
55
0
Order By: Relevance
“…As noted in the ‘Talc’ section above, a small retrospective comparison study of talc via chest drain versus blood patch was inconclusive. 39 Two further small retrospective series of patients unfit for surgery with recurrence or persistent air leak found long-term recurrence of 16.0% 49 and 16.1% 50 with no comparator groups.…”
Section: Resultsmentioning
confidence: 99%
“…As noted in the ‘Talc’ section above, a small retrospective comparison study of talc via chest drain versus blood patch was inconclusive. 39 Two further small retrospective series of patients unfit for surgery with recurrence or persistent air leak found long-term recurrence of 16.0% 49 and 16.1% 50 with no comparator groups.…”
Section: Resultsmentioning
confidence: 99%
“…Blood patch pleurodesis, whereby a patients own blood is instilled through an existing chest tube, has emerged as an effective option for treatment for pneumothorax with reported pneumothorax recurrence rates of 15.6–18.2% (99). The advantage of this technique is the almost complete absence of typical pleurodesis-associated side effects such as pain and fever (100). The introduction of blood in an otherwise sterile cavity may, however, lead to an increased risk of infectious complications.…”
Section: Introductionmentioning
confidence: 99%
“…Instillation of chemical agents, doxycycline, and talc has been recommended in cases of prolonged air leakage. [3] Pleurodesis is an easy, safe, effective, and well-tolerated treatment for secondary pneumothorax [6,7,9,11] Some studies have reported the effectiveness of pleurodesis using a 50% glucose solution in treating pneumothorax with prolonged air leakage after a surgical procedure or chylothorax [12,14,15]. To my knowledge, only a few studies have investigated patients with secondary pneumothorax in whom surgery is contraindicated [13].…”
Section: Discussionmentioning
confidence: 99%
“…Pleurodesis for malignant pleurisy and pneumothorax with prolonged air leakage is simple, effective, and safe [6][7][8][9][10]. OK-432, autoblood, and minocycline are often used in pleurodesis for refractory pneumothorax [6,7,9,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation